Kedudukan Hukum Simantek Kuta dalam Penyelesaian Sengketa Tanah Adat Suku Karo di Kabupaten Karo - Pelawi, Roy Andalan (Medan Resource Center, 2023)
This study aims to examine the position of simantek kuta within the current structure of the Karo indigenous community, its legal relationship with customary land, and its authority in resolving land disputes. The research utilizes the legal sociology method, employing analytical descriptive analysis. Secondary data from primary, secondary, and tertiary legal sources are collected through library research and field studies. Simantek kuta, as a kuta leader, was replaced by the system defined in Law Number 5 of 1979 and Law Number 6 of 2014 on Village Administration, aiming to establish legal certainty and standardize village governance. Simantek kuta holds a joint leadership role with the village head in managing and utilizing customary land of the Karo people. In resolving land disputes, simantek kuta acts as a leader, employing traditional Karo customary law methods such as purpur sage and runggu. Differentiating between government leadership led by the village head and adat leadership led by simantek kuta, the Karo people have established regulations within the Kuta leadership system. It is recommended to establish a Regional Regulation in Karo Regency to protect and recognize the existence of customary land, preventing conflicts and disputes. Preserving the dispute resolution system through peaceful means and family-oriented decisions based on Karo customary law, such as purpur sage and runggu, is crucial. Mutual respect for dispute resolution decisions should be fostered within the community.